Methyl-Sulfonyl-Methane (MSM)-Induced Acute Angle Closure. Issue 4 (April 2015) - Hwang, Jeremy C.; Khine, Kay T.; Lee, Jennifer C.; Boyer, David S.; Francis, Brian A.
<x xml:space="preserve">Abstract</x> Purpose: To report the first case of presumed bilateral acute angle closure (AAC) secondary to ingestion of the dietary supplement, methyl-sulfonyl-methane (MSM). Patient: A 35-year-old woman presented with bilateral AAC 1 week after starting multiple dietary supplements, one of which contained MSM. Ultrasound biomicroscopy demonstrated bilateral anterior rotation of the iris-lens diaphragm, ciliary body edema, and choroidal effusion. Four days after discontinuation of the supplements, her angle closure and uveal effusion resolved, and her best-corrected vision recovered to 20/20 bilaterally. Discussion: Sulfa-based drugs have been reported to cause AAC, choroidal effusion, and ciliary body edema. In our patient, the coincidence of bilateral AAC with choroidal and ciliary body effusion that began 1 week after starting dietary supplements was suspicious for drug-induced AAC. The dietary supplement Basic Detox Nutrients contains MSM, the only constituent in the patient's medication list with a sulfonyl moiety. Given the similarities in chemical structure and clinical presentation, we postulate that MSM induces AAC in a manner similar to mechanisms previously described for other sulfa-based drugs. Conclusions: As MSM continues to be used and studied for its anti-inflammatory and antioxidative properties, investigators and marketers will need to be cognizant of its potential to cause AAC and provide proper warning to consumers.